2020
DOI: 10.1093/milmed/usaa137
|View full text |Cite
|
Sign up to set email alerts
|

Maternity Leave Length Impact on Breastfeeding and Postpartum Depression

Abstract: Introduction In January 2016, the U.S. Department of Defense increased the duration of paid maternity leave for active duty service members from 6 weeks to 12 weeks. Our study aims to determine the impact of maternity leave length on breastfeeding duration and postpartum depression rates in active duty service members. Materials and Methods An institutional review board-approved survey of 9 questions was given to patients at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…28,33 One military study of 857 mothers found a statistically significant increase in breastfeeding duration through 9 months ( P =.003) and breastfeeding exclusivity through 6 months ( P =.016) after the policy change increased the length of maternity leave from 6 to 12 weeks 31 ; another military study of 214 active-duty mothers found a 5.4%, nonstatistically significant, increase in the percentage of service members who breastfed up to 6 months after the same policy change. 32 One cross-sectional study found that a 1-week increase in total maternity leave was associated with a 4.2-day increase in breastfeeding duration ( P =.022). 38 Shortened durations of maternity leave and early return to work contribute to the decrease in infants who are exclusively breastfed, which was suggested in all 23 included articles.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…28,33 One military study of 857 mothers found a statistically significant increase in breastfeeding duration through 9 months ( P =.003) and breastfeeding exclusivity through 6 months ( P =.016) after the policy change increased the length of maternity leave from 6 to 12 weeks 31 ; another military study of 214 active-duty mothers found a 5.4%, nonstatistically significant, increase in the percentage of service members who breastfed up to 6 months after the same policy change. 32 One cross-sectional study found that a 1-week increase in total maternity leave was associated with a 4.2-day increase in breastfeeding duration ( P =.022). 38 Shortened durations of maternity leave and early return to work contribute to the decrease in infants who are exclusively breastfed, which was suggested in all 23 included articles.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen articles (56.5%) used national survey data, including the National Immunization Survey, the National WIC Infant and Toddler Feeding Practices Study Survey, and the Centers for Disease Control and Prevention's Infant Feeding Practices Study II, to analyze the relationship between maternity leave and breastfeeding duration. [18][19][20][21][22][23][24][25][26][27][28][29][30] Eight articles (34.7%) used local survey data, of which two articles (8.7%) studied activeduty military mothers, 31,32 three (13.0%) used statewide survey data, [33][34][35] and three (13.0%) were cohort studies at local hospitals. [36][37][38] The remaining two articles (8.7%) provided narrative information based on previous literature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations